Effectiveness of Using a Combination of Media in a Multi-Stage Filter For Processing Cisadane River Water - Sephiana, Lidya; Saifullah, Saifullah; Munandar, Erik (MSJ : Majority Science Journal, 2025)
Water filters are tools that are widely used to purify water so that the dirt contained in it is reduced. Limited clean water causes many people to use water from rivers. One of the rivers that is still often used by people for MCK (Bathing, Washing, Toilet) activities is the Cisadane River, Tangerang Regency. This study aims to determine the best composition in improving water quality pH, TDS, ammonia, and iron levels in a multi-stage filtration device. This study was conducted in January-March 2025. Testing of iron (Fe) levels was carried out at the Serang Regency Health Laboratory UPT. This study consists of three stages, namely filter tool design, tool testing, and water quality testing. The water quality measured is the physical and chemical parameters (pH, TDS, ammonia, and iron levels). The trial method used was a Completely Randomized Design with 2 treatments (combinations) of 3 replications, namely combination 1 (15 cm silica sand, 15 cm rubble, 15 cm activated carbon, 15 cm zeolite stone, 10 cm sponge) and combination 2 (20 cm silica sand, 10 cm rubble, 20 cm activated carbon, 10 cm zeolite stone, 10 cm sponge). Based on research data, it shows that the use of multilevel filtration devices with two different combinations can improve water quality pH, TDS, ammonia, and iron levels. The best treatment was obtained by combination 2 because it was able to reduce TDS, ammonia and iron levels by 73%, 100%, and 98% respectively and increase the pH value towards more neutral. All results of filtration water quality tests from both compositions were significant (p> 0.5), but both compositions still had a good effect in improving water quality.